The Role of Surveillance in the Management of Small Renal Masses - Alessandro Volpe (The Scientific World Journal)
Incidentally detected, small renal masses (SRMs) have been increasing significantly in recent years due to the widespread use of improved cross-sectional imaging. A significant number of incidental SRMs are diagnosed in elderly patients who are more likely to undergo imaging for other medical issues. The natural history of SRMs has not been historically well understood because most masses are surgically removed soon after diagnosis.